zipRealty : leading a start-up to the next level (A) - Chatman, Jennifer, (SAGE Knowledge. Cases., 2017)
Start-up company zipRealty is a real estate brokerage that leveraged the Internet on the belief that selling or buying a home could be faster, easier, and more efficient than was possible with existing approaches to residential home transactions. Despite zipRealtys successes, the company experienced a series of external and internal challenges.